EXPOSITION OF CATHOLIC THEOLOGY IN HOPKIN’S POETRY - Abdullah Ansari (International Journal of Multidisciplinary Research and Studies, 2021)
In 1863, Hopkins went to Oxford and while reading Classics began his lifelong friendship with Robert Bridges, who published his poems posthumously in 1918. His earliest diaries are full of sensitive and close observation on nature and poetic imagery. With zest he studied words and the ’Onomatopoetic theory’ of the origin of language. Thus early he envinced for combined meaning, sound, and suggesfion which was later turned to an exhaustive account in his poetry. Most of the poems he himself attempted between 1862 and 1868 were either derivative or abortive. As an exception, in the The Habit of Perfection we see with what si^ill and genuine poetic passion he could handle the conventional forms and metres." The Oxford Movement, began in 1833, was a great effort to establish the Authority and Catholicity of the English Church and to refuse into it something of the medieval spirit of intellectual and natural piety. Together with William Addis and the other undergraduates, Hopkins became an ardent Puseyite and Ritualist.